Educational Reform in Indonesia (2017)
This work is a part of a research project that is still in process. The central theme of the research project revolves around the educational reform that was raised in 1999 and the changes that occur in public Higher Education Institutions during 2000 and 2017 in Indonesia. The objective of this work is to identify the impacts of the changes made by public HEIs before the educational reform related to quality and equity in education and the commercialization of university knowledge. In this research project, a bibliographic analysis and field work are carried out between 2015 and 2017, where individual surveys of key people are carried out. The research thoroughly examines data from the University of Indonesia.